EFEK LIKOPEN TERHADAP TIKUS PUTIH GALUR SD (Sprague Dawley) YANG DIINDUKSI PARASETAMOL DENGAN MELIHAT AKTIVITAS SGPT DALAM DARAH - Risha Maysara; Sapto Yuliani (Universitas Ahmad Dahlan, 2011)
Liver is one of the most important organ for drug metabolism in the body. The damage to the liver can be marked by increased activity of the enzyme alanine aminotransferase (ALT) in the blood. Lycopene is an antioxidant that has the ability to eliminate free radicals and detoxifies electrophilic compounds that damage can be prevented. The purpose of this research is to know whether lycopene can inhibit the increase alanine aminotransferase activity of SD (Sprague Dawley) rats induced by parasetamol. This experiment using 20 male rats Sprague Dawley. They were divided into 4 groups. Group I is a healthy control (baseline) was only given aquadest, group II were given paracetamol as pain control, group III and IV are treatment group were each given lycopene with a dosage 15 µg/kg BW and 30 µg/kg BW for 21 days. On 19th day group II, as well as all treatment groups induced paracetamol. The blood sampling was performed on orbital sinus on 19th day (before induced by paracetamol) and on 21th day or two days after induced paracetamol to know the difference alanine aminotransferase activity. The data were analyzed using non-parametric statistical methods with Kruskal-Wallis test followed by Mann-Whitney test with 95% confidence level. The result has showed that the lycopene doses 15 µg/kgBW had alanine aminotransferase activity of 130.10 ± 11.83 U/I and lycopene doses 30 µg/kgBW had alanine aminotransferase activity of 106.46 ± 2.36 U/I. If compared with paracetamol control had alanine aminotransferase activity of 92.53 ± 2.57 U/I, should take a summary that the lycopene doses 15 ìg/kg BW and 30 ìg/kg BW couldn’t decrease alanine aminotransferase activity on SD (Sprague Dawley) male rats.